2017
DOI: 10.1039/c7ra06612k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biobased blends of poly(lactic acid) (PLA) and poly(glycerol succinate-co-maleate) (PGSMA) with balanced performance prepared by dynamic vulcanization

Abstract: A sustainable and industrially viable method for toughening poly(lactic acid) by dynamic vulcanization using glycerol and succinic acid based polyesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 68 publications
3
53
0
Order By: Relevance
“…The difference in behaviors was due to the decreased crystallization ability of PLA caused by the incorporation of ENR. In addition, the intensity of the tan δ peak of the PLA/G0.15 blend was significantly lower than that of the PLA/ENR blend, perhaps due to restricted chain mobility of PLA caused by interaction between anhydride in ENR‐g‐MA and hydroxyl groups in the PLA . Peak intensity, however, increased with increasing grafted MA content.…”
Section: Resultsmentioning
confidence: 93%
“…The difference in behaviors was due to the decreased crystallization ability of PLA caused by the incorporation of ENR. In addition, the intensity of the tan δ peak of the PLA/G0.15 blend was significantly lower than that of the PLA/ENR blend, perhaps due to restricted chain mobility of PLA caused by interaction between anhydride in ENR‐g‐MA and hydroxyl groups in the PLA . Peak intensity, however, increased with increasing grafted MA content.…”
Section: Resultsmentioning
confidence: 93%
“…Addition of nanocrystalline cellulose caused an increase in the composite stiffness and ultimate tensile strength and a reduction in the elongation at break. Similar PGSMA copolymers were also used to prepare blends with PLA and poly(butylene succinate) with enhanced mechanical properties [27][28][29]. The synthesized copolymers were thermally stable materials, and dynamic mechanical analysis confirmed that the Tg of copolymers increased by increasing the maleic anhydride content (Figure 1).…”
Section: Synthesis Of Pgsuc Polyesters With Side Groups and Pgsuc Copmentioning
confidence: 93%
“…The synthesized copolymers were thermally stable materials, and dynamic mechanical analysis confirmed that the Tg of copolymers increased by increasing the maleic anhydride content (Figure 1). [27]. Published by The Royal Society of Chemistry.…”
Section: Synthesis Of Pgsuc Polyesters With Side Groups and Pgsuc Copmentioning
confidence: 99%
See 2 more Smart Citations